Adherence by a primary healthcare clinic in KwaZulu-Natal to the national HIV guidelines - Nnaemeka Uzodike; Andrew Ross; Ogbonnaya Harbor (South African Family Practice)
Background: The decentralisation of antiretroviral therapy (ART) to primary health care (PHC) was rolled-out in South Africa in March 2010. PHC staff members are expected to initiate ART, monitor patients, and detect and refer patients with adverse events or virological failure to designated referral hospitals. The aim of this study was to assess the monitoring and referral of patients on ART who were being managed at a PHC clinic.